Helping Others Helps Me: Prosocial Behavior and Satisfaction With Life During the COVID-19 Pandemic - Espinosa, Juan C.; Antón, Concha; Grueso Hinestroza, Merlin Patricia (Frontiers in Psychology, 2022)
Prosocial behavior (PsB) and its effects have been analyzed in times of crisis and natural disasters, although never before in the face of such exceptional circumstances as those created by the COVID-19 pandemic. This research analyzes the role of PsB on satisfaction with life (SWL)in Colombia, considering the negative emotional impact of events that began in February 2020. We conduct an exploratory analysis using a sample of Colombia’s general population (N = 2574; 53.2% women) with an average age of 44.66 years (SD = 15.36). Using the Classification Tree technique, we find that engaging in one or more PsBs (e.g., donating money or sharing food) enhances SWL and decreases the impact of negative emotions such as pessimism, indecisiveness, and irritability that have emerged during the COVID-19 pandemic. These findings are significant because they confirm the importance of life satisfaction as a personal resource for coping with complex situations and provide evidence of the benefits of PsB on one’s well-being.